The use of Mazk intelligent tutor in the process of teaching and learning geography applied in elementary education - Moro, Francielli F.; Valeriano, Edilene C. F.; Silva, Viviane I. da; Pozzebon, Eliane; Friggo, Luciana B. (Anais do Workshop on Advanced Virtual Environments and Education (WAVE); 2018: Anais do I Workshop on Advanced Virtual Environments and Education, 2018)
The use of Information and Communication Technologies related to sustainability in the educational environment has enabled positive impacts in schools. In this sense, the present article describes an experience with the use of the MAZK Intelligent Tutor System, as it assists in the students 'learning and in the teachers' practice obtaining real-time evaluative results, thus educating for sustainability, since it dispenses the use of paper in the application of the evaluative activities. A pilot test was developed with geography content within the virtual environment containing explanations, examples and exercises was developed to assist in the teaching-learning process and evaluation. Through the analysis of applied questionnaires the reports show that the intelligent tutor obtained positive results with its clarity and practicality being considered simple and dynamic favoring the interpersonal relationship between teachers and students.